Differences in DPOAE and AABR in Noise‐Exposed Infants in the Neonatal Intensive Care Unit. (23rd August 2013) - Liao, Selena; MacArthur, Carol; Martin, William H.; Mace, Jess; Lubianski, Troy; Steyger, Peter
Abstract : Objectives: 1) Describe the differences in distortion product otoacoustic emissions (DPOAE) and automated auditory brainstem response (AABR) results in premature infants in the neonatal intensive care unit (NICU) with noise exposure. 2) Discuss optimal newborn hearing screen protocols for capturing at‐risk NICU graduates. Methods: Prospective observational outcomes study from August to the present. Subjects: Admissions to the NICU, <37 weeks gestational age. Setting: NICU. Outcome Measurements: DPOAE, AABR, and follow‐up audiometry collected by the Oregon Early Hearing Detection and Intervention (EHDI) program. Independent variables: Sound pressure levels and cumulative sound dosage. Preliminary analyses: This dataset represents preliminary data from an ongoing study with a target enrollment of 150 over 12 months. Results: The average sound pressure level per individual admission ranged from 57.4 to 67.8 dBA. DPOAE demonstrated a greater rate of abnormalities in the high frequency range of 4000‐10000 Hz (40‐45%) compared to lower frequencies (10‐15%). AABR generated only a 5% rate of referrals; however, 50% of DPOAEs obtained showed abnormal results in at least 2/3 of the high frequencies tested. Conclusions: All infants received sound exposures that substantially exceeded AAP guidelines. More abnormalities were found on DPOAE than AABR, with a significantly higher rate in the high frequencies compared to lower frequencies, consistent with possible noise‐induced cochlear dysfunction. Neonatal intensive care units should consider adding DPOAE to their hearing screen protocols so that infants at risk for noise‐induced hearing loss are not missed.